Neandertal camps and hyena dens. Living floor 150A at Grotta dei Santi (Monte Argentario, Tuscany, Italy). (April 2020) - Spagnolo, Vincenzo; Crezzini, Jacopo; Marciani, Giulia; Capecchi, Giulia; Arrighi, Simona; Aureli, Daniele; Ekberg, Isak; Scaramucci, Sem; Tassoni, Laura; Boschin, Francesco; Moroni, Adriana
Highlights: A Mousterian living floor is analysed with a spatial and interdisciplinary approach. A complex processual history was reconstructed by a taphonomic perspective. A brief hyena den shortly preceded the structured Neandertals camp. Faunal processing, lithic production and shell-related activity were found. Multipurpose hearth-related activity areas were found. Abstract: Grotta dei Santi represents a very suitable investigation field for carrying out an inquiry into the Neandertal behaviour at a high-resolution time scale, in order to obtain data useful for the "functional" reading of the economic and settling strategies. This cave opens into the Monte Argentario Promontory (southern coast of Tuscany, central Italy), almost at sea-level, at the base of a limestone falaise about 50 m high. During MIS 3, when Neandertals occupied the site, there was a wide plain in front of the cave. Excavations carried out by the University of Siena over the last 13 years brought to light several Mousterian occupation phases represented, most of the times, by thin living floors separated from one another by sterile sediments. However, another "occupant", the spotted hyena ( Crocuta crocuta ), left clear traces in the cave in layers other than those occupied by humans. Although there usually is a clear-cut stratigraphic separation, a partial overlapping between the human and hyena occupations is sometimes documented, owing to their closeness in time. This is the case for the uppermost "living floor" of layer 150, which is the object of our study. A multidisciplinary integrated analytic methodology was applied, including lithic technology, taxonomic analysis of faunal remains, taphonomy, use-wear analysis and spatial analysis by means of a GIS platform. This approach allowed us to detect a set of parameters useful for identifying activities due to each of these two predators individually, which provided substantial information about their behaviours.